If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2=2(w+2)-5w
We move all terms to the left:
-2-(2(w+2)-5w)=0
We calculate terms in parentheses: -(2(w+2)-5w), so:We get rid of parentheses
2(w+2)-5w
We add all the numbers together, and all the variables
-5w+2(w+2)
We multiply parentheses
-5w+2w+4
We add all the numbers together, and all the variables
-3w+4
Back to the equation:
-(-3w+4)
3w-4-2=0
We add all the numbers together, and all the variables
3w-6=0
We move all terms containing w to the left, all other terms to the right
3w=6
w=6/3
w=2
| 1x-4=8x-12 | | -18w+10w=24 | | 19=a-5 | | 24+56x=180 | | 42/120=x/100 | | 10h+(-4h)=(-12) | | 2(x+5)=5(2x-6)+3 | | 33=9–2x | | x/3+16=42 | | 9x+5+x–2=23 | | a÷15=25 | | 3x-0.01x=122 | | (2+3)+42x(5−3)= | | (X+5)(x+5)=17 | | 2y+y+10+50=180 | | 88–7=3x+5x+4–x | | 2x+0.09x=126 | | 8x+4=-32+13x | | -5(3x-23)=2(x-1)-87 | | f/2.75=6 | | 0=-d/2+5 | | 9x+6=-92-8x | | -36+x=5 | | 11=w/3+6 | | 1/2(x-2)=64+7x | | 14x+20+x=180 | | v+1/2=-3/6 | | 64=x*40 | | 5+2x=3(-x+9)-32 | | 2x-14=5x-10+x+20 | | 5(x-4)=3(2x-1)-1 | | 7d+6=90 |